MENINGKATKAN KEMAMPUAN FISIK MOTORIK KASAR ANAK USIA 5-6 TAHUN DENGAN MEDIA DINGKLIK PADA KELOMPOK B TK DWP GEDANG KULUT CERME GRESIK - Riyadlotus Sholichah; Nur Aliyah (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2022)
There are many things that affect the physical motor skills of children, not only the atmosphere and learning environment at school, but also the conditions of the community and family environment which also have a major influence on motor intelligence. This research was conducted to find out how the use of walking chair / chair props to improve the gross motoric abilities of children aged 5-6 years of group B TK DWP Gedang Kulut Cerme Gresik and to find out whether the use of walking chair / cloister props can improve children's gross motor skills. 5-6 years old Group B TK DWP Gedang Kulut Cerme Gresik. For data collection, the authors used the PTK method carried out in two cycles, each cycle carried out 1 meeting, namely in Cycle I in March, Week III and Cycle II in March, Week IV, in accordance with the changes to be achieved, namely 80% or 25 children from 28 students in Group B TK DWP Gedang Kulut Gedangkulut Cerme Gresik. In the observation activity of playing with outdoor play equipment (walking chair / cloister) starting from cycle I, cycle II, it was seen that the students' ability to play with outdoor play equipment (walking chair / cloister) was very good, this was in accordance with the percentage of observation results Playing with outdoor games (walking chair / dingklik) in cycle I and cycle II are almost the same, namely the highest percentage per student is 100%. The percentage of criteria in the first cycle (BW = 10.7%, MB = 25%, BSH = 30.7%, BSB = 28.5%) becomes (BW = 0%, MB = 14.2%, BSH = 36.4 %, BSB = 39.2%) in cycle II. Overall percentage from 70.54% in cycle I to 81.25% in cycle II.